2015
DOI: 10.1088/2041-8205/804/1/l21
|View full text |Cite
|
Sign up to set email alerts
|

Small Scatter and Nearly Isothermal Mass Profiles to Four Half-Light Radii From Two-Dimensional Stellar Dynamics of Early-Type Galaxies

Abstract: We study the total mass-density profile for a sample of 14 fast-rotator early-type galaxies (stellar masses ≲ ≲ ⊙ M M 10.2 log * 11.7). We combine observations from the SLUGGS and ATLAS 3D surveys to map out the stellar kinematics in two dimensions, out to a median radius for the sample of four half-light radii R e (or 10 kpc) and a maximum radius of 2.0-6.2 R e (or 4-21 kpc). We use axisymmetric dynamical models based on the Jeans equations, which allow for a spatially varying anisotropy; employ quite general… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
178
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(214 citation statements)
references
References 47 publications
30
178
6
Order By: Relevance
“…First, in galaxies dominated by baryons there is no systematic evidence for large cores or lowered DM density profiles (e.g., Cappellari et al 2015). Second, in galaxy clusters the stars dominate the total mass budget within their half-light radii, yet the DM tends to be under-dense compared to predictions.…”
Section: Motivation: Contraction Of Sidm Halosmentioning
confidence: 98%
“…First, in galaxies dominated by baryons there is no systematic evidence for large cores or lowered DM density profiles (e.g., Cappellari et al 2015). Second, in galaxy clusters the stars dominate the total mass budget within their half-light radii, yet the DM tends to be under-dense compared to predictions.…”
Section: Motivation: Contraction Of Sidm Halosmentioning
confidence: 98%
“…Therefore, the circular velocity of a typical ETG decreases between 0 and 10 percent when going from 0.5−1 R eff , where it is traced by CO, to the outer regions, where it is traced by H i. Cappellari et al (2015) recently found that the mass profiles of a sample of 14 ETGs can be well described by a nearly isothermal power law ρ tot ∝ r −γ with an average logarithmic slope γ = 2.19 with remarkable small scatter in γ. The small decrease in circular velocity we observe is consistent with such mass profiles.…”
Section: Comparison To the Co K-band Tfrmentioning
confidence: 95%
“…We use the parameter k to take into account different galaxy mass profiles: k ∼ 4 for the Hernquist profiles assumed by the model (see Barausse 2012, for details), but k ∼ 10 (or even larger) is possible if a core is present. On the other hand, strong lensing and accurate dynamical modelling have shown that the mass profiles of intermediate-mass, early-type galaxies are consistent with nearly isothermal profiles down to (at least) tenths of the effective radius (e.g., Cappellari et al 2015, and references therein). These have k ∼ 1.…”
Section: The Normalisation Of the Scaling Relations And The Role Of Smentioning
confidence: 99%